Wine as an Investment Opportunity - Majerčáková, Daniela; Mittelman, Alexandra; Greguš, Michal (European Journal of Economics and Business Studies, 2019)
Market development with non-traditional commodities is not as developed and widespread as the market with traditional commodities. There is much information regarding investments into antiquarian objects but there is not so much regarding other types of commodities. The traditional slovak investor is an investor into classic investment products with lower risk and lower revenue at the same time. As Warren Buffett said, price does not matter, but value matters. In case of some commodities, with we can gain the high appreciation with a small investment, too, despite the high risk. We have to look forward and to think about the future with non-traditional investments as it is the long-term investment. It represents goods that are little liquid, and there is an inactiveness sometimes needed, but on the other hand it is still necessary to follow the market. There are more and more possibilities of investments with the fast-changing world. Sometimes we can get interesting revenues from some irrational investments. The aim of this paper is to analyze conditions of the market with possibilities to invest into non-traditional commodities, where also the investments into wine belong. We have used the description of alternative investments, analysis of facts and conditions as well as the possibilities of non-traditional investments in Slovakia to reach this aim. On the basis of observing the price development, we have made recommendations for the traditional slovak investor with the positive relationship to non-traditional investments and with the positive relationship to risk.
Keywords: commodity, wine, non-traditional investing, market